Biological activities of organic extracts and specialized metabolites from different parts of Cryptomeria japonica (Cupressaceae) – A critical review. (February 2023) - Lima, Ana; Arruda, Filipe; Janeiro, Alexandre; Medeiros, Jorge; Baptista, José; Madruga, João; Lima, Elisabete
Abstract: Forest operations and wood industry generate large amounts of residues that are discarded in the field and cause environmental pollution. However, these biomass residues are still raw materials to obtain value-added products, such as essential oils, organic/aqueous extracts and resins that are among the great natural sources of bioactive metabolites. Thus, in recent years, the scientific community is giving special attention to their valorization. To date, different uses of biomass residues have been proposed, such as a source of renewable energy, fertilizers, animal feed and bioactive molecules. In this context, Cryptomeria japonica biomass residues (e.g., bark and its exudate, heartwood, sapwood, leaves, cones and roots) represent a source of diverse specialized metabolites (e.g., sesqui-, di-, tri- and sesquarterpenes, flavonoids, lignans and norlignans) with potential application in different fields, particularly in the agrochemical, food, cosmeceutical, pharmaceutical, phytomedicine and esthetic, due to their valuable multi-bioactivities determined over the last decades. Thus, this review provides an overview of the reported biological activities of organic extracts/fractions and their specialized metabolites obtained from different parts of C. japonica, in order to encourage the alternative uses of C. japonica wastes/byproducts, and implement a sustainable and circular bioeconomy. Graphical abstract: Image 1 Highlights: Cryptomeria japonica has been investigated for long time owing to its industrial importance. C. japonica residues (e.g., bark) are an inexpensive source of natural bioactive compounds. Terpenes and norlignans from C. japonica have therapeutic/pest-control properties. Ferruginol, sandaracopimarinol, cryptotrione and sequirin C are relevant C. japonica compounds. Green extraction techniques for obtaining C. japonica bioactive compounds should be exploited.